Evaluation of Bread Wheat (Triticum aestivum L.) Germplasm at Kafa Zone, South West Ethiopia - Kochito Gebremariam; Sintayehu Alamirew; Wosene Gebreselassie (Advances in Agriculture)
Bread wheat germplasm has wide genetic diversity, which means it can withstand a lot of biotic and abiotic stresses. Despite the presence of bread wheat germplasm diversity in Ethiopia, wheat production in the Kafa Zone is significantly lower than the national average. The ultimate goal of this research was to determine the genetic diversity of grain yield and yield components of bread wheat. One hundred bread wheat accessions with 3 local checks were evaluated in augmented randomized complete block design at Kafa Zone, Gewata Woreda Shupa site, during the 2018–19 growing season. The mean performance of the accessions revealed that accession number 29812 yielded more grain than the others. Spike length, number of seeds per spike, biomass yield, and harvest index all had moderate genotypic coefficients of variation. Spike length, number of seeds per spike, thousand seed weight, biomass yield, and harvest index all had moderate-to-high heritability and also all the above-listed traits had moderate-to-high genetic advance as a percentage of the mean. This means that practical improvement of these essential traits can be achieved by effective and satisfactory selection. Grain yield has positive correlations with grain filling period, number of productive tillers, spike length, number of seeds per spike, thousand seed weight, and biomass yield. The principal component analysis grouped all of the traits into four main components. Seven clusters and one ungrouped accession were formed from the accessions. Cluster IV and cluster VI had the greatest intercluster distance (D2 = 104.77) among the clustered groups, suggesting the probability of selecting a parental genotype for hybridization. However, the current result is merely indicative and cannot be used to draw firm conclusions. As a result, the experiment should be replicated in different locations and seasons for greater consistency.